A new species of Aquilegia (Ranunculaceae) from Sardinia (Italy) - Bacchetta, Gianluigi; Brullo, Salvatore; Congiu, Angelino; Fenu, Giuseppe; Garrido, José Luis; Mattana, Efisio (Phytotaxa, 2012)
The new species Aquilegia cremnophila (Ranunculaceae) from the Italian island of Sardinia is here described and illustrated. It occurs in shady rocky crevices, near the upper parts of Mt. Corrasi (Supramontes Region), where it is a member of chasmophilous communities. This species is morphologically, phenologically, ecologically and genetically well differentiated from the other Sardinian taxa, showing some relationships mainly with A. nugorensis, an endemic species of Central-Eastern Sardinia. Its conservation status is examined. A key of all taxa present in Sardinia is also provided.